EFEKTIVITAS KOMUNIKASI ANTARPRIBADI REMAJA BERMASALAH DAN PETUGAS DI PANTI SOSIAL BINA REMAJA (PSBR) BUDI SATRIA PROVINSI KALIMANTAN SELATAN - Agus Mulyana; Artini Suparmo; Deli Anhar (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2014)
The background of this research is that the client / student / student is a troubled teen who is identified can always disturbing growth of the public who are not can not be expected in the community. So researchers are interested in knowing how kefektivitas komunikasiny between troubled teens with the officers in Children's Social Development of Youth (PSBR) Budi Satria South Kalimantan Province.  The method used is descriptive quantitative method with the object of study is the effectiveness of interpersonal communication officer and troubled teens in the PSBR. Theories used include Interpersonal Communication Theories, effective interpersonal communication is a humanistic perspective, and understanding of youth. Its population of 125 troubled teens by using the formula as much as 30 teenagers Taro Yamani. The results showed the effectiveness of the communication officers in troubled teens and Teens Children's Social Development (PSBR) Budi Satria South Kalimantan high category (65.36%) as there are in the range of 60.1 to 80%, the level of communication among troubled teens or clients with the officers established a good communication and efktiv. The implications of this study is that the pattern of development that has been used in the Children's Social Development of Youth (PSBR) Budi Satria South Kalimantan province have been said better.